Customer Relationship Management and Utilization of Digital Marketing Media as a Strategy for Increasing the Marketing Performance of MSMEs (Micro, Small and Medium Enterprises) - I. G. N. Andhika Mahendra; I. G. N. Anom Maruta; Ayun Maduwinarti (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The conditions of the Covid-19 Pandemic since the beginning of 2020 have been followed by policies limiting community activities and strict controls that paralyzed almost all sectors of the community's economy, and decreased trade. This condition affects developments in the micro, small and medium enterprises (MSMEs) sector. This study, which took purposive sampling of MSME managers in the Surabaya area and its surroundings, explains the tactical steps taken by MSME entrepreneurs to maintain and develop their business through customer relationship management which is supported by the use of digital marketing media. The research data were collected through a questionnaire, and an analysis of the mean difference test was carried out through the paired t test, which proved that the probability of sales volume using digital marketing media was greater than conventional marketing media; the level of consumer response to MSMEs when using digital marketing media is greater than the use of conventional media; the intensity of interaction between MSME marketers and consumers who utilize digital marketing media is higher than conventional media; and opportunities for MSMEs to promote and offer back to consumers who use digital marketing media are greater than when using conventional media. It can be concluded that the implementation of the customer relationship management strategy directly affects marketing performance, and CRM which is supported by the use of digital marketing media has an effect on marketing performance. This study found that there are obstacles to using digital media as marketing media, namely the skills and abilities of MSME managers in designing products and designing digital marketing media features.